2019
DOI: 10.1038/s41590-019-0419-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic programming underpins B cell dysfunction in human SLE

Abstract: Systemic lupus erythematosus (SLE) is characterized by the expansion of extrafollicular pathogenic B cells derived from newly activated naïve cells. Although these cells express distinct markers, their epigenetic architecture and how it contributes to SLE remains poorly understood. To address this, we determined the DNA methylomes, chromatin accessibility and transcriptomes from five human B cell subsets, including a newly defined effector B cell subset from SLE and healthy subjects. Our data define a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
171
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(185 citation statements)
references
References 67 publications
13
171
0
1
Order By: Relevance
“…The emergence of CD11c + DN B cells is not unique to active SLE, and even healthy subjects display this B cell subset in the blood and tonsil albeit at a lower frequency . The differentiation mechanism by which resting naïve B cells become activated and differentiate into CD11c + DN B cells in humans is currently under extensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of CD11c + DN B cells is not unique to active SLE, and even healthy subjects display this B cell subset in the blood and tonsil albeit at a lower frequency . The differentiation mechanism by which resting naïve B cells become activated and differentiate into CD11c + DN B cells in humans is currently under extensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…162 This demonstrates how the epigenome serves as a record of developmental history. 162 Analysis of the epigenetic program in B-cell subsets representing a range of differentiation stages revealed that an SLE disease state existed in the naive B-cell subset, suggesting the SLE environment was establishing a heritable phenotype that could impact later differentiation trajectories. Enhancers are the primary regulatory elements that are different between cell types.…”
Section: Epigenetic Regulation Of Sle B-cells Implications For Undmentioning
confidence: 98%
“…Some of the strongest evidence for altered epigenetic programs comes from studies of twins discordant for SLE that have distinct DNA methylation patterns in CD4 + T-cells. 161,162 This indicates that B-cells may be under the control of epigenetic processes that are distinct from other immune lineages, even within the same autoimmune disease. 161,162 This indicates that B-cells may be under the control of epigenetic processes that are distinct from other immune lineages, even within the same autoimmune disease.…”
Section: Epigenetic Regulation Of Sle B-cells Implications For Undmentioning
confidence: 99%
See 2 more Smart Citations